Perbedaan Adversity Quotient dan Kematangan Emosi Remaja SMP ditinjau dari Jenis Kelamin - Ayub Djafar; IGAA Noviekayati; Sahat Saragih (Lembaga Penelitian Universitas YARSI, 2018)
To face the problems faced in adolescent life required adversity quotient (fighting power). Adversity quotient is an important understanding of what teenagers need to achieve success that is the ability to survive and face difficulties in every problem. This ability will only be owned by individuals who have the ability to take control and respond to a difficulty or pressure positively. In addition it also needs emotional maturity so that teenagers reach the level of emotional development and no longer display the childish emotional patterns. A mature teenager develops a good value system, proper self-concept and has stable emotional behavior. The purpose of this research is to know the difference of adversity quotient and emotional maturity of junior high school adolescent in terms of gender, relationship between adversity quotient and emotional maturity of junior high school, and difference of emotional maturity and adversity quotient of junior high school in Kendari. The population in this study were all junior high school students in Kendari City and the sample in this study amounted to 150 students of junior high school in Kendari. The research instrument is the scale of adversity and the scale of emotional maturity. The result of quantitative analysis with t-Test proves that there is no difference adversity quotient and emotional maturity of junior high school teenagers (p = 0.747 0.05) t = 0.110. The result of quantitative analysis with Pearson correlation test proves that there is a relationship between adversity quotient and emotional maturity of junior high school in Kendari (p = 0.046 0.05). And there is no difference between the emotional maturity of junior high school male and female sex. (p = 0.435 0.05) t arithmetic = 1.544.